Bīta rāga, arathāta, Jīwana srīmāna Bābā Jawāhara Siṅgha jī - Cakrawaratī, Indara Siṅgha (SAMP early 20th-century Indian books project ;, 1924)
Biography of Jawāhara Siṅgha, religious leader of Namdhari sect in Sikhism.